“Significant silences” and the politics of National Reconciliation in Chater’s Crossing the Boundary Fence - Tagwirei, Cuthbeth (Taylor & Francis (Routledge), 2016)
The article explores Patricia Chater’s Crossing the Boundary Fence (1988) within the framework of Macherey’s (1978) concept of “significant silences”. I argue that in her representation of the decolonisation of Zimbabwe, the writer circumvents pertinent areas that are central to any discussion of the colonial history of Zimbabwe and the liberation war against colonialism. Among the areas the text is silent on is the role of white people in institutionalising racism in the colony and the contributions of ZAPU and the Ndebele during the war of liberation. These silences are informed by a reconciliation agenda which makes silence integral to its realisation.